Procedures and practices: reflections following 20-years working on a community project in southeast India. Issue 6 (18th August 2022) - Winchester, Peter
ABSTRACT: These notes are aimed at anyone who wants to become or join an NGO in India. They are based on experience working in the Krishna Delta as a UK registered charity: the Divi Seema Foundation (DSF). Dire poverty and relative wealth live side by side in the same villages. Central concerns are lack of year-round employment, lack of essential services to the poorest areas and the overall indifference of local government officials. Effective NGOs require a stable support system, continuity, reliable field officers, regular monitoring, and adjustments when necessary.